Os elementos da organização da ação pedagógica na educação infantil: a criança na atividade docente - Machado, Cristiane Schroeder (2012)
This work was developed at Master s Post Graduation Program in Education at Santa Maria Federal University, in the line of research of School Practices and Public Policies(LP2). The general aim was to investigate the elements of teaching acts organization and the concepts of children subjected to it. For that, I tried to: (a) identify the elements that guide the teaching activity with children at the teaching organizing action; (b) think about it with the teachers; (c) and also try to understand how the teachers feel the activity of the child in such organization. Using historic-cultural approach, the qualitative research was organized in a reflexive-problematic-dialogical way based on Freire s theory that constituted itself during the work by the observation of the participants, arguments of scenes and discussion groups, having as subjects of the research the teachers of a City School of Children Education in Santa Maria. For data collection records in field diary were made, pictures, filmings, scene discussing and in the discussion group, the analysis and thoughts beginning from the picture-filming and images of Tonucci s work (1988). In the data analysis, having as a basis Leontiev s Activity Theory elements of the teaching action organization were performed such as planning, routine and activity. The work made possible a reflection about the teaching organization and also how the activities are being organized in the field of research. The analyses proofs signs of an unbelief by the teachers in the potential of the children that go to that institution and rises possibilities for the justifications and/or comprehension of the teaching conceptions about the activity in the organization of teaching action. Understanding children as participants, active subjects and capable of developing themselves and produce culture, we contribute for the thinking and discussing of the teachers of Children s Education about the children, active subjects in the process of building the daily schooling action. Moreover, we can provide spaces and times in which the children experience their childhood fully in the teaching community context, that is, in the public or private institutions of Children Education.